2022
DOI: 10.5853/jos.2022.00941
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment for Posterior Circulation Stroke: Ways to Maximize Therapeutic Efficacy

Abstract: The efficacy of endovascular treatment (EVT) in patients with posterior circulation stroke has not been proven. Two recent randomized controlled trials failed to show improved functional outcomes after EVT for posterior circulation stroke (PC-EVT). However, promising results for two additional randomized controlled trials have also been presented at a recent conference. Studies have shown that patients undergoing PC-EVT had a higher rate of futile recanalization than those undergoing EVT for anterior circulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 110 publications
(173 reference statements)
0
15
0
Order By: Relevance
“…31,32 Moreover, removal of the thrombus within ICAD-related LVO may be challenging because of lack of contact between the catheter tip and thrombus with contact aspiration. 33 In patients undergoing percutaneous intervention for ST-segment-elevation myocardial infarction, aspiration thrombectomy has not been demonstrated to improve clinical outcomes in a metaanalysis of 3 randomized trials, 34 and the benefit of primary aspiration for ICAD-related LVO remains to be validated. 31 Differences in respondent preferences by country income were observed for all techniques.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Moreover, removal of the thrombus within ICAD-related LVO may be challenging because of lack of contact between the catheter tip and thrombus with contact aspiration. 33 In patients undergoing percutaneous intervention for ST-segment-elevation myocardial infarction, aspiration thrombectomy has not been demonstrated to improve clinical outcomes in a metaanalysis of 3 randomized trials, 34 and the benefit of primary aspiration for ICAD-related LVO remains to be validated. 31 Differences in respondent preferences by country income were observed for all techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, another two RCTs, BAOCHE (Basilar Artery Occlusion Chinese Endovascular Trial) and ATTENTION (Endovascular Treatment for Acute Basilar Artery Occlusion), showed the benefit of EVT for acute VBAO 3 4. The favorable outcome (90 day modified Rankin Scale (mRS) score of 0–3) rate in these four RCTs in the EVT groups varied from 42% to 46.4% 5. Therefore, finding strategies to improve the clinical outcome of acute VBAO after EVT is critical.…”
Section: Introductionmentioning
confidence: 94%
“…In other MT studies targeting patients with basilar artery occlusion, they also classified the patients as vertebrobasilar artery occlusion without separating the patients with vertebral artery occlusion. 7 …”
Section: Authors' Response To the Lettermentioning
confidence: 99%